2022
DOI: 10.1186/s40001-022-00723-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the BTK/NF-κB signaling pathway and related cytokines in different stages of neuromyelitis optica spectrum disorders

Abstract: Objective Neuromyelitis optica spectrum disorders (NMOSDs) are blindness-causing neuritis; their pathogenesis is still not fully elucidated. Although it has been determined that Bruton tyrosine kinase (BTK) and NF-κB are associated with NMOSD, the changes that occur in different periods remain unknown. The study aimed to demonstrate the changes in the BTK/NF-κB pathway and related chemokines in different stages of NMOSDs. Methods A total of 32 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 73 BTK/NF-κB pathway was found to be activated in NMOSD patients in the acute phase, but not in the remission phase, compared with healthy controls. 70 This provided the preliminary evidence that BTK inhibition could be a potential therapy to ameliorate the pathological progression of NMOSDs. However, the precise mechanisms of BTK involvement are needed to be further confirmed.…”
Section: The Immune-related Mechanisms Of Btk Inhibition In the Centr...mentioning
confidence: 87%
See 1 more Smart Citation
“… 73 BTK/NF-κB pathway was found to be activated in NMOSD patients in the acute phase, but not in the remission phase, compared with healthy controls. 70 This provided the preliminary evidence that BTK inhibition could be a potential therapy to ameliorate the pathological progression of NMOSDs. However, the precise mechanisms of BTK involvement are needed to be further confirmed.…”
Section: The Immune-related Mechanisms Of Btk Inhibition In the Centr...mentioning
confidence: 87%
“…68,69 In addition, B cells are also present in meningeal inflammation areas, causing pathological changes in brain cortex. 70,71 BTK inhibition, but not anti-CD20 B-cell depletion, succeeded to eliminate B cells in the meningeal inflammation. 71 Therefore, BTK inhibition, with its selectivity and reversibility, is promising to serve as an alternative MS therapy.…”
Section: Beyond Bcr Signaling Pathwaymentioning
confidence: 94%
“…However, the regulation of chemokine levels in NMOSD patients is contradictory in the literature. For instance, while one study reported elevated levels of the systemic neutrophil-related chemokine CXCL2 in AQP4-IgG-seropositive patients compared to controls [ 25 ], another study found decreased serum CXCL2 levels [ 22 ]. Our study also found decreased local CXCL2 secretion in retinas treated with NMOSD IgG compared to control IgG.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, chemokines CCL2 and CCL5 have been found to be increased in response to AQP4-IgG treatment in isolated rat astrocyte cultures [ 21 ]. However, the implications for CXCL2 and CXCL10 remain ambiguous, as divergent findings have been reported in the serum of NMOSD patients across various studies [ 22 , 23 , 24 , 25 ]. Although chemokines CCL3 and CCL4 are known to be elevated in the serum of NMOSD patients, their concentrations within the retinal milieu are yet to be explored [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%